Myers Briggs based Model of Indicator/MBTI- based Social Competence and Teacher Personality Model based on Information Technology - Supadi, (International Journal of Psychosocial Rehabilitation, 2020)
Myers Birggs Type Indicator (MBTI) is a test or test that is designed to measure and see a person's psychological condition in seeing who is there and making decisions. The research objective is to develop an MBTI- based teacher's social competency and personality model that will be integrated with Information technology. The method used to solve problems using Research and Development. To find out in full the needs of Teacher Competencies. The results to be achieved have 2 (two) stages: The first stage, the study will present a needs analysis and model design; and Second Stage, the research tested the model that had been designed, until the final results were obtained on the MBTI-based teacher social competency development model. In general, it is estimated that the majority of elementary school (SD) teachers in the Special Region of Jakarta have extrovert personality types and the majority of respondents have high personalities and social characteristics.